Inhibitory effect of isavuconazole, ketoconazole, and voriconazole on the pharmacokinetics of methadone in vivo and in vitro. Issue 4 (25th December 2018) - Shen, Leibin; Wang, Jun; Yi, Yongdong; Ye, Chenmin; Wang, Rongrong; Xia, Guojun; Yu, Chengyang; Tu, Fuyang; Xu, Jingxuan; Zheng, Zhiqiang
Abstract: The aim of this study was to investigate the possible effect of orally administered isavuconazole, ketoconazole, or voriconazole on the pharmacokinetics of methadone in rats. Twenty Sprague–Dawley (SD) rats were divided randomly into four groups: Group A (control), group B (5 mg/kg isavuconazole), group C (5 mg/kg ketoconazole), and group D (5 mg/kg voriconazole). A single dose of methadone was administrated half an hour later. Methadone in plasma concentrations and its metabolite EDDP in microsomes were determined by ultra‐high‐performance liquid chromatography–tandem mass spectrometry method (UPLC–MS/MS), and pharmacokinetic parameters were calculated by DAS version 3.0. The Cmax of methadone in groups C and D increased to 2.7‐fold and 5‐fold, respectively. While AUC increased in three groups and group D increased the most. Also, isavuconazole, ketoconazole, and voriconazole showed inhibitory effect on human and rat microsomes. The inhibition ratios of isavuconazole, ketoconazole, and voriconazole in rat liver microsome were 97.87%, 96.74% and 78.9%, respectively ( p < 0.01), while in human liver microsome, inhibition ratios were 86.97%, 96.46%, and 53.11%, respectively. And the IC50 for inhibition activity of isavuconazole, ketoconazole, and voriconazole in rat microsomes were 7.76 μM, 8.33 μM, and 4.45 μM, respectively. Our study indicated that taking methadone combine with ketoconazole, isavuconazole, or voriconazole could reduce the metabolism rate of methadone and prolong the pharmacological effects in vivo and in vitro. Abstract : The results showed that after co‐administration with isavuconazole, ketoconazole and voriconazole, the three drugs could increase methadone plasma levels and some of its pharmacokinetic parameters (Cmax, AUC) due to its inhibitory effect of the activity of CYP3A4. In detail, voriconazole have the strongest ability of changing pharmacokinetic characteristics of methadone among them, while ketoconazole is relatively weaker and isavuconazole is minimum. For clinical use, when methadone co‐administration with isavuconazole, ketoconazole or voriconazole, dose adjustment of methadone should be considered